Identifying aroma‐active compounds in coffee‐flavored dairy beverages. Issue 3 (17th February 2022) - Mahmud, M. M. Chayan; Keast, Russell; Mohebbi, Mohammadreza; Shellie, Robert A.
Abstract : Abstract: Coffee aroma is a complex mixture of volatile compounds. This study characterized the important aroma‐active compounds associated with consumer liking in formulated coffee‐flavored dairy beverages. Nine coffee‐flavored dairy beverages were formulated: low fat–low coffee; medium fat–low coffee; high fat–low coffee; low fat–medium coffee; medium fat–medium coffee; high fat–medium coffee; low fat–high coffee; medium fat–high coffee; and high fat–high coffee. Regular coffee consumers, ( n = 231) used a nine‐point hedonic scale to rate acceptance of aroma. Volatile compounds were extracted by head space‐solid phase micro‐extraction (HS‐SPME) and analyzed by gas chromatography‐mass spectrometry‐olfactometry (GC‐MS‐O) using a modified frequency (MF) approach. Fifty‐two aroma‐active compounds were detected. Thirty‐one aroma‐active compounds were considered important compounds with MF‐value ≥ 50%. The total number of aroma‐active compounds and their intensity were affected because of fat and coffee concentration. Partial least squares regression (PLSR) was performed to determine the relationship between aroma‐active compounds and liking. PLSR analysis identified three groups of compounds regarding liking. Twenty‐five compounds were associated with positive liking, for example, 2‐(methylsulfanylmethyl) furan (coffee like). Sixteen compounds were negatively associated with liking, for example, 2‐methoxyphenol (bacon, medicine like). Eleven detected compounds had no association with liking, for example, butane‐2, 3‐dione (butter, fruit like). Practical Application : The result of this study may be applied to formulate coffee‐flavored dairy beverages to maximize consumer acceptance and aroma‐liking. This study suggested too low coffee concentration is not desirable. Too much fat affects aroma release and/or alters the characteristic coffee flavor which negatively affects consumer acceptance.